Pharmacological and toxicological aspects of fentanil: Review and synthesis of evidence (Research, Society and Development, 2025)
Drug abuse is a current and worrying topic, as it is a global public health problem. The indiscriminate and recreational use of fentanyl has become a growing concern worldwide, contributing significantly to the opioid overdose crisis. Although it is an effective analgesic, its potential for addiction and the risks associated with inappropriate use are alarming. The objective of this study was to analyze the pharmacological and toxicological aspects as a consequence of indiscriminate use, through an integrative literature review. The methodology included an integrative literature review, through publications in the LILACS, SCIELO and PUBMED databases, between the years 2014-2024, using the descriptors opioids, fentanyl and drug abuse, considering as inclusion criteria articles indexed in national and international journals accessed in full text in Portuguese and English; and as exclusion criteria articles that did not fit the objectives, course completion papers, dissertations, theses and editorial notes. This study found a total of 200 articles in the three databases analyzed during the research. However, after the inclusion and exclusion criteria, 15 articles were selected to compose the literature review. The analysis of the 15 studies allowed us to identify that fentanyl is an extremely potent synthetic opioid, used to treat intense pain, especially in cases of cancer or after surgeries, but its effects on the other hand can cause very exorbitant dependence when administered incorrectly. Its main antagonist is naxolone.